A Significant Association of Upper Limb Muscle Strength with Thyroid Function in Overweight and Obese Population: A Study of the Sixth Korea National Health and Nutrition Examination Survey (KNHANES 2014-2015) - Jeongmin Lee; Kwanhoon Jo; Jeonghoon Ha; Dong-Jun Lim; Jung Min Lee; Sang-Ah Chang; Moo Il Kang; Min-Hee Kim (International Journal of Endocrinology)
Background. As skeletal muscle is one of main targets of thyroid hormone signalling, an association of thyroid function and muscle strength could be expected. The aim of study is to evaluate the association of free thyroxine (FT4) and thyrotropin (TSH) with upper limb muscle strength, measured by hand grip strength, in subjects with normal FT4 from national representative data. The study utilized the sixth edition of the Korea National Health and Nutrition Examination Survey. After exclusion of subjects with FT4 level out of normal range, a history of thyroid disease or cerebral disease, restricted activity, and incomplete data, a total of 3503 were recruited (age range 19–80 years, 51% male). FT4 positively correlated with upper limb muscle strength (β coefficient = −12.84, p<0.001), while TSH did negatively (β coefficient = −0.37, p=0.002). After adjusting for confounding factors, statistical significance disappeared. However, among subjects with BMI above 23 kg/m2, a negative correlation of TSH with upper limb muscle strength was found in a younger age group (19–39 years old) (β coefficient = −0.56, p=0.021), while FT4 positively correlated with upper limb muscle strength (β coefficient = 3.24, p=0.019) in an older group (above 40 years old). In overweight and obese subjects, a significant association of thyroid function with upper limb muscle strength was observed in nation-wide representative data. High TSH in a younger group and low FT4 in an older group could be risk factors for decreased upper limb muscle strength in obese population.